Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Resto Campus di Jalan Air Dingin Kota Pekanbaru - Tiara Dinanti; Rosmayani Rosmayani (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
This study aims to analyze the effect of service quality on customer satisfaction at Resto Campus located on Air Dingin Street, Pekanbaru City. Service quality is an important factor in creating a good experience for customers, so that it can increase satisfaction and encourage customers to revisit and recommend the restaurant to others. This study uses a quantitative approach with a survey method, where the data were obtained through the distribution of questionnaires to customers who have made purchases at Resto Campus. The service quality variable was measured through the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, while customer satisfaction was assessed through the suitability of expectations, intention to revisit, and willingness to recommend. The collected data were then analyzed using statistical analysis techniques to examine the relationship between the two variables. The results of the study indicate that service quality has a significant effect on customer satisfaction. The service provided was considered fairly good by some customers, however, there are still several aspects that need improvement, especially related to facility cleanliness, accuracy of service delivery, and employee attention to customer needs. Customer satisfaction has also not been fully achieved optimally because there are still customers who feel that the service does not meet their expectations. Therefore, a comprehensive improvement in service quality is highly necessary so that customer satisfaction can increase and the sustainability of the restaurant business can be maintained